Teacher Strategies through Blended Learning System to Foster Student Reading Skill at MTSN 1 Pasuruan - Putra, Krisna Aditya (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Learning strategies have an essential role in achieving learning objectives, especially in improving students' reading skills. The pandemic made the Government Issue new rules for implementing the learning system in the classroom using a blended learning system. This system also affects the teacher's teaching strategies as a facilitator in the classroom to help the process of students' thinking skills improve reading skills in a text or video. This research was conducted with the aim of; (1) identifying the teaching strategies carried out by teachers through a blended learning system to foster students' reading skills at MTsN 1 Pasuruan, (2) finding out the strengths and weaknesses in teaching reading skills through a blended learning system. In this research, the researcher uses a qualitative approach, and the type of research is a field study using three instruments: observation, interview, and documentation. The data obtained have been processed in several ways. The first is to reduce the data, the second is to display the data findings, and the last is to describe the conclusions. Participants in this study were English teachers of class VIII and class VIII students at MTsN 1 Pasuruan. This study indicates that three strategies are learning used by English teachers through a blended learning system, namely Question-Answer Relationships, Think aloud, and reciprocal teaching. As for the way the teachers implement strategies for the online teaching stage of the Question-answer relations teacher through WhatsApp and E-learning groups, and during the offline teaching stage, the teacher uses think aloud and reciprocal teaching in the classroom.